Understanding the dynamics of black carbon and associated contaminants in glacial systems. (30th January 2014) - Hodson, Andrew J.
<x xml:space="preserve">Abstract</x> More than one billion people depend upon glaciers for water, yet this exploitation is seldom underpinned by science‐led water management practice. Previous work has detected that glaciers store and then subsequently release contaminants to downstream ecosystems, revealing a potentially harmful legacy that needs to be managed in conjunction with contemporary atmospheric pollution and climate change. Remarkably, while several classes of harmful organic pollutants have been considered in this context, almost no attention has been given to black carbon, a dark aerosol that is host to several adsorbed contaminants and that greatly increases glacier melt by enhancing the absorption of solar radiation. The future impact of black carbon upon glacier melt and contaminant release cannot be managed until we know how much historical black carbon is stored in Earth's glaciers. Further, as the residence time of ice within many mountain glaciers is between 100 and 1000 years, major changes in these impacts can be anticipated in the near future. A case is therefore made for using glacier dynamic models to understand the distribution of postindustrial, contaminated ice within glaciers, so that their impacts upon melt water quantity and quality can be forecast. A research framework is proposed that ranges from high flux, dynamic glaciers which are replete with postindustrial ice, to low flux, polar glaciers which are unlikely to become replete before they disappear. Research into the processing of contaminants following their melt‐out is also required, because microbial processes will lead to their bioflocculation and biodegradation on glacier surfaces. Conflict of interest: The author has declared no conflicts of interest for this article.